Does Capital Intensity Moderate The Effect Of Financial Distress And Operational Performance Tax Avoidance In Regional-Owned Enterprises In Water Supply? - Hapsari, Diah Oktavia; Wibowo, Puji (Educoretax, 2024)
Tax avoidance is a legal practice by companies as an effort to reduce the tax burden distributed to the state. This is commonly done by companies, both private and government-owned. Regional-Owned Enterprises in Water Supply as a company owned by the Regional Government has a dual role, namely providing public goods and generating profits. This research aims to analyze the influence of financial difficulties, service effectiveness, and operational efficiency on tax avoidance with capital intensity as a moderating variable in Regional-Owned Enterprises in Water Supply. This research uses quantitative methods with secondary data obtained using documentation data collection methods. The sample in this study was selected based on purposive sampling and resulted in 117 companies spanning the period 2019-2022. The data analysis technique in this research uses multiple linear regression analysis using the Eviews version 12 program with a significance level of 5%. The results of this study show that financial difficulties and service effectiveness have a significant negative effect on tax avoidance, but operational efficiency has an insignificant positive effect on tax avoidance. The aggressiveness of Regional-Owned Enterprises in Water Supply towards tax avoidance is not as high as other organizations that are completely profit-oriented. This is possible because human resources do not understand taxation. In addition, direct supervision by the Regional Government makes management more alert to violations of statutory regulations. Capital intensity can weaken the influence of financial difficulties on tax avoidance and strengthen the influence of operational efficiency on tax avoidance. The greater the number of company fixed assets, the greater the depreciation expense, management can choose the depreciation method that is most profitable for the company.